Management of coastal hazardous sites : a case study of Reynisfjara beach, Iceland - Truter, Anika, 1992- (2017)
The rapid growth of the tourism industry in many parts of the world has led to increasingly complex questions regarding ways to ensure effective management that leaves tourists satisfied and safe, and at the same time leaves host communities with economic and social benefits. In Iceland, inbound tourism increased by almost 73% from 2010-2016, and nature-based tourism continues to be a major draw. One popular beach, Reynisfjara, has been the site of three deaths since 2007 and numerous close calls as visitors are caught by surprise by dangerous sneaker waves and dragged offshore. The projected continued increase in inbound tourism has prompted the multiple stakeholders involved in the management of the beach to search for more effective management tools. This thesis aims to document current safety and site use issues at Reynisfjara Beach, to explore the most effective communication management tools to keep tourists safe, and to recommend a decision-making governance structure that involves local stakeholders. First, I conducted semi-structured interviews with key management stakeholders within Iceland to document stakeholders’ perceptions of safety at Reynisfjara Beach and to understand how current use of the site affects supportive industries/organizations. Second, using results from a literature analysis of hazardous sites around the world and the semi-structured interviews, I conducted a guiding principles framework analysis to make recommendations for potential future management options and decision-making arrangements at the beach. Recommendations for management tools include the presence of a ranger and increased visibility of warning signs. Highlights from the guiding principles framework analysis show that the lack of decision-making structure can hinder the efficacy of any management tool implementation. A stakeholder group called “Friends of Reynisfjara” (Vinir Reynisfjöru) is suggested and specific organization flow and funding scenarios are discussed. For tourism at Reynisfjara to be considered ...